Angiotensin receptor blockers and risk of myocardial infarction: systematic review. Issue 7521 (23rd September 2005) - McDonald, Michael A; Simpson, Scot H; Ezekowitz, Justin A; Gyenes, Gabor; Tsuyuki, Ross T
Abstract: Objective To evaluate the effect of angiotensin receptor blockers on the risk of myocardial infarction in patients at risk for cardiovascular events. Design Systematic review of controlled trials of angiotensin receptor blockers. Data sources Medline, Embase, Cochrane central register of controlled trials, hand search, and contact with investigators. Selection of studies Predefined criteria were used to select controlled clinical trials comparing use of angiotensin receptor blockers with angiotensin converting enzyme (ACE) inhibitors or placebo in patients at risk for cardiovascular events. Data were extracted for patients' characteristics, interventions, quality of trials, and rates of myocardial infarction. Results 19 studies with 31 569 patients were included in the analysis. Two studies investigated the use of angiotensin receptor blockers in hypertensive patients, four studies in patients with diabetes and nephropathy, 10 studies in patients with heart failure, and three in patients with recent myocardial infarction or ischaemic syndrome. 11 studies of 21 062 patients allowed for comparison between angiotensin receptor blockers and placebo; nine studies of 10 625 patients allowed for comparison between angiotensin receptor blockers and ACE inhibitors. Use of angiotensin receptor blockers was not associated with increased risk of myocardial infarction compared with placebo (odds ratio 0.94, 95% confidence interval 0.75 to 1.16) nor with increased risk of myocardial infarction compared with ACE inhibitors (1.01, 0.87 to 1.16). Conclusions Treatment with angiotensin receptor blockers was not associated with a significantly increased risk of myocardial infarction. The 95% confidence intervals do, however, not exclude an increase of up to 16% in the risk of myocardial infarction or a reduction in risk of up to 25%. Until further information specifically dealing with this issue is available from large prospective trials, our findings may alleviate recent concerns over the safety of this class of medications.